Analisis Risiko Penularan Tuberculosis Paru Akibat Faktor Perilaku dan Faktor Lingkungan pada Tenaga Kerja di Industri - Tri Martiana, M.Atoillah Isfandiari, Muji Sulistyowati, Ira Nurmala (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: Tuberculosis, with its increasing burden of morbidity and mortality, remains a major health problem in Indonesian community. Patients with droplet nuclei and their environment are two important infectious factors. Unhealthy working environment has become a promoting factor of TB infection in industry. One study revealed that TB prevalence among industrial worker was as high as 0.9%, and this suggests probable contagious agents (TB) circulating at workplacesObjective: This study was conducted to analyze the risk of TB infection among industrial workers in Gresik Subdistrict, East Java Province.Method: This study is an analytic observational study with case-control design. A total of 125 respondents were recruited in the study, 25 cases and 100 controls. Cases were industrial workers who suffered from TB and being treated on TB medication in primary health center (Puskesmas). Controls were healthy industrial workers. Cases and controls were matched by age, working place and duration of working. Variables studied included smoking habit, use of mask, exposure to sunlight, and dust at work place.Result: Risk factors of TB infection included not using mask (OR=2.01), absence of sunlight at workplace (OR=1.195), and exposure to dust at work place (OR=1.338). However, none of the factors were statistically significant.Conclusion: Despite the statistical insignificant results of this study, several factors were identified as probable factors of TB infection at work place. Further research with larger sample size is warranted.Keywords: risk analysis, TB infection, industry